2020
DOI: 10.14796/jwmm.c470
|View full text |Cite
|
Sign up to set email alerts
|

Seeking Substantiality: Evaluation of Public Attitudes toward Resilient Wastewater Reuse Management

Abstract: Because of Iran's limited water resources, maximum usage of available water resources is a high priority. In this case study of Tehran, Iran, academic and industrial applications of the strengths, weaknesses, opportunities and threats (SWOT) approach provide an analysis of the main challenges of wastewater reuse. One possible solution for dealing with water crises is to reuse water in different consumption areas. An important step in this regard is to evaluate the public attitude toward different usages of rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
(17 reference statements)
0
6
0
Order By: Relevance
“…It is observed that adults (99.1%) have a higher tendency to support the utilization of recycled wastewater for both potable and non-potable water compared to senior adults (97.6%) who are reluctant to utilize recycled wastewater as potable nor non-potable water. According to Daghighi et al (2020), one's willingness to utilize recycled wastewater be it for potable or non-potable uses typically decrease. This trend probably can be explained by how younger people have different views towards new technologies and are highly interested and supportive of living a sustainable life compared to the older generations as the younger have a whole life ahead of them.…”
Section: Resultsmentioning
confidence: 99%
“…It is observed that adults (99.1%) have a higher tendency to support the utilization of recycled wastewater for both potable and non-potable water compared to senior adults (97.6%) who are reluctant to utilize recycled wastewater as potable nor non-potable water. According to Daghighi et al (2020), one's willingness to utilize recycled wastewater be it for potable or non-potable uses typically decrease. This trend probably can be explained by how younger people have different views towards new technologies and are highly interested and supportive of living a sustainable life compared to the older generations as the younger have a whole life ahead of them.…”
Section: Resultsmentioning
confidence: 99%
“…38,39 Country-level studies have also highlighted differences in opinion regarding the use of wastewater. [40][41][42][43][44][45][46][47] Providing consumers with information regarding recycled water can help ameliorate their negative perceptions about it. 48 Bakopoulou et al 49 reported that using the media to provide information on wastewater treatment and reuse practices could encourage more people to accept the water source.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Across gender, the acceptance of using reclaimed water has been studied in many countries and is usually increasing along a trajectory (Figure 5) from direct to indirect physical contact with the least preferred option being its use in drinking water reservoirs or to replenish groundwater . Variations between gender are locationspecific and can point at a higher rate of acceptance by men, as shown for example by Daghighi et al (2020) (Figure 6).…”
Section: Acceptance Of Wastewater Reusementioning
confidence: 99%